2020
DOI: 10.2147/idr.s278084
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk Factors and Outcomes of Carbapenem-Resistant Enterobacteriaceae Infection After Liver Transplantation: A Retrospective Study in a Chinese Population</p>

Abstract: Background There is an increasing prevalence of carbapenem-resistant Enterobacteriaceae (CRE) infection after liver transplantation (LT). Improved understanding of the risk factors and outcomes of CRE infections can help us to develop effective preventive strategies and even guide early treatment of high-risk LT patients. Methods This was a retrospective study involving all Chinese adult patients who underwent LT between December 2017 and September 2019 in our center. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Previous studies also showed that the infectious site was more prone to biliary duct infection in solid organ transplantation and biliary complication was the prognostic risk factor of carbapenem-resistant Enterobacteriaceae infection after liver transplantation. 28 , 29 Our study acquired the similar conclusion. In our study, the biliary infection could be an independent prognostic risk factor of 90-day death for immunosuppressed elderly people (OR: 4.406, 95%CI: 1.794–10.821, p =0.001).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies also showed that the infectious site was more prone to biliary duct infection in solid organ transplantation and biliary complication was the prognostic risk factor of carbapenem-resistant Enterobacteriaceae infection after liver transplantation. 28 , 29 Our study acquired the similar conclusion. In our study, the biliary infection could be an independent prognostic risk factor of 90-day death for immunosuppressed elderly people (OR: 4.406, 95%CI: 1.794–10.821, p =0.001).…”
Section: Discussionsupporting
confidence: 83%
“… 21–23 In our previous study, the incidence of CRE infection was 6.7% within 30 days after LT, and patients with CRE infections had significantly lower 180-day survival rates (51.5% vs 92.4%, p < 0.001). 24 Since the use of carbapenems is associated with an increased risk of CRO infection, we analyzed the incidence of CRO infection in this study. 25 We found that 13.3% of patients developed CRO infections within 30 days after LT. And, the CRO infection rate did not differ significantly between the carbapenem and non-carbapenem groups.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for CRE colonisation and/or infection are similar to those identified for all CR Gram-negative infections [10], being associated with the host (e.g., older age), hospitalisation (e.g., number of previous hospitalisations, emergency department stay[2 days prior to intensive care unit admission), treatment (e.g., previous exposure to antibiotics) and procedures (e.g., invasive procedures/indwelling devices), recent surgery, immunocompromised status and organ transplantation [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], chronic skin ulcers [13], along with mechanical ventilation and patient movement between hospital departments [26].…”
Section: Burden Of Carbapenem-resistant Enterobacteralesmentioning
confidence: 99%